2007
DOI: 10.1002/cne.21564
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of bursting neurons in the CA1 region and the subiculum of the rat hippocampus

Abstract: We performed patch-clamp recordings from morphologically identified and anatomically mapped pyramidal neurons of the ventral hippocampus to test the hypothesis that bursting neurons are distributed on a gradient from the CA2/CA1 border (proximal) through the subiculum (distal), with more bursting observed at distal locations. We find that the well-defined morphological boundaries between the hippocampal subregions CA1 and subiculum do not correspond to abrupt changes in electrophysiological properties. Rather,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
123
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 118 publications
(143 citation statements)
references
References 44 publications
17
123
1
Order By: Relevance
“…An expected outcome of such a wide distribution of intrinsic properties is that the participation probability and temporal patterning of CA1 neurons during spontaneous ripples can be only partially dictated by the upstream CA3 neurons, and that the intrinsic properties bias the participation probability and sequential recruitment of neurons in response to optogenetic activation. In line with this reasoning, pyramidal neurons vary extensively in their responses to in vitro current injection (38,39). Thus, even if every neuron experienced an identical ramp of input current (from the CA3 population during spontaneous ripple events or from the light stimulus during synthetic ripples), diverse spike patterns and sequential activity would still ensue due to intrinsic neuronal/ circuit heterogeneity.…”
Section: Discussionmentioning
confidence: 94%
“…An expected outcome of such a wide distribution of intrinsic properties is that the participation probability and temporal patterning of CA1 neurons during spontaneous ripples can be only partially dictated by the upstream CA3 neurons, and that the intrinsic properties bias the participation probability and sequential recruitment of neurons in response to optogenetic activation. In line with this reasoning, pyramidal neurons vary extensively in their responses to in vitro current injection (38,39). Thus, even if every neuron experienced an identical ramp of input current (from the CA3 population during spontaneous ripple events or from the light stimulus during synthetic ripples), diverse spike patterns and sequential activity would still ensue due to intrinsic neuronal/ circuit heterogeneity.…”
Section: Discussionmentioning
confidence: 94%
“…Bursting cells are more numerous deep in the layer, whereas regular spiking cells are more common superficially . However, it is also reported that the percentage of bursting cells is linearly correlated to the position along the proximodistal axis, with approximately 10% of bursting neurons in proximal Sub and more than 50% in distal Sub (Jarsky et al, 2008;Kim and Spruston, 2012). Both cell types may actually only reflect a single class of neurons sharing a burst mechanism that is stronger in some cells (Staff et al, 2000).…”
Section: Principal Cellsmentioning
confidence: 87%
“…Subicular pyramidal cells project to a variety of cortical and subcortical structures (Stewart and Wong, 1993;Amaral and Witter, 1995) and they have been shown to be differentially distributed in the proximo-to-distal and deep-to-superficial axes of the subiculum (Greene and Totterdell, 1997;Staff et al, 2000;Harris et al, 2001;Menendez de la Prida et al, 2003;Jarsky et al, 2008). Future studies will have to map the target structures of bursting and regular firing cells to unravel the physiological implications of cell-specific plasticity at hippocampal output synapses.…”
Section: Discussionmentioning
confidence: 99%